Endovascular Treatment of Distal Posterior Cerebral Artery Infectious Aneurysm - Bohara, Manoj; Bista, Prakash (Nepal Journal of Neuroscience, 2020)
Intracranial infectious aneurysms are rare entities accounting for approximately 1- 6 % of all cerebral aneurysms and have high propensity of rupture associated with mortality. The principal risk factor is infective endocarditis and the management includes antimicrobial treatment with or without obliteration of the aneurysm by microsurgical or endovascular means. We present a young patient with intracranial infectious aneurysm who was successfully treated with endovascular coil embolization. A 20-years-old female with history of rheumatic heart disease presented with subarachnoid hemorrhage due to rupture of IIA associated with infective endocarditis. Cerebral angiogram revealed right distal posterior cerebral artery aneurysm. Echocardiography showed vegetation in mitral valve and blood culture was positive for Enterococcus faecalis. Antibiotic treatment was administered for 6 weeks. The follow-up angiogram showed an enlarging aneurysm. So, the patient underwent endovascular coil embolization of the aneurysm preserving the parent artery. There were no post-procedure deficits. Intracranial infectious aneurysm should be considered as a differential diagnosis in a patient with infective endocarditis presenting with focal neurological deficits or altered consciousness. Early diagnosis and individualized approach are the key to successful treatment and endovascular treatment is an effective modality for such lesions.